2012
DOI: 10.1016/s0034-7094(12)70181-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of The Efficacy of Bupivacaine Soaked in Gelfoam® at the Iliac Crest Bone Graft Site

Abstract: This study has demonstrated that bupivacaine soaked in gelfoam at the iliac bone graft harvest site reduced postoperative parenteral opioid usage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…On contrary, local application of bupivacaine soaked gelfoam at the site of iliac graft operations failed to reveal any significant difference in VAS pain scores in comparison to the use of parenteral opioid although the required narcotic dosage was significantly less in bupivacaine group at 24 and 48 hours (14).…”
Section: Discussionmentioning
confidence: 72%
“…On contrary, local application of bupivacaine soaked gelfoam at the site of iliac graft operations failed to reveal any significant difference in VAS pain scores in comparison to the use of parenteral opioid although the required narcotic dosage was significantly less in bupivacaine group at 24 and 48 hours (14).…”
Section: Discussionmentioning
confidence: 72%
“…To minimize postoperative donor site pain, preemptive analgesia strategies have been employed including intravenous analgesics, intraoperative local anesthetic sponges, nerve blocks, and local anesthetic infusion pumps (Wilkes and Thomas, 1994; Hahn et al, 1996; Hoard et al, 1998; Blumenthal et al, 2005; Singh et al, 2005; Singh et al, 2007; Coulthard et al, 2008; Dashow et al, 2009; Ouaki et al, 2009; Isyanov and Suresh, 2009; Sbitany et al, 2010; Meara et al, 2011; Gamli et al, 2012; Visoiu, 2014; Muzaffar et al, 2016). Intraoperative use of bupivacaine at the iliac crest donor site has been shown to delay the onset of pain, decrease postoperative opioid use, and lead to earlier ambulation (Hoard et al, 1998; Dashow et al, 2009; Gamli et al, 2012). Recent studies of indwelling pain catheters have reported conflicting findings regarding length of hospitalization after iliac crest bone graft (ICBG) for secondary alveolar reconstruction (Sbitany et al, 2010; Meara et al, 2011; Muzaffar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The advent of techniques such as minimally invasive trephine drill harvest and placement of continuous-infusion pain pumps has made outpatient ABG an increasingly feasible and cost-effective procedure 4,11–13 . Multiple methods have been described to control donor site pain in patients receiving ABG including opioids, non-steroidal anti-inflammatory drugs, local anesthetic injections or nerve blocks, 14–16 anesthetic sponges, 15,17 and placement of continuous-infusion pain pumps 8,12,13,18–23 …”
mentioning
confidence: 99%